2012
DOI: 10.1128/iai.00167-12
|View full text |Cite
|
Sign up to set email alerts
|

VirK Is a Periplasmic Protein Required for Efficient Secretion of Plasmid-Encoded Toxin from Enteroaggregative Escherichia coli

Abstract: ABSTRACTDespite the autotransporter (AT) moniker, AT secretion appears to involve the function of periplasmic chaperones. We identified four periplasmic proteins that specifically bound to plasmid-encoded toxin (Pet), an AT produced by enteroaggregativeEscherichia coli(EAEC). These proteins include the 17-kDa Skp chaperone and the 37-kDa VirK prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…We have shown that a virK mutant in C. jejuni NCTC 11168 displays decreased growth, enhanced motility and biofilm formation, and a strongly hydrophobic cell surface – the latter phenotype shared only with the peb4 mutant ( Figures 1A–C,E ). This supports the hypothesis that VirK in C. jejuni may play a more general role in OM or cell surface biogenesis than reported in E. coli , where VirK is necessary, and potentially specific, for Pet toxin secretion (Tapia-Pastrana et al, 2012), a system absent in C. jejuni. …”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We have shown that a virK mutant in C. jejuni NCTC 11168 displays decreased growth, enhanced motility and biofilm formation, and a strongly hydrophobic cell surface – the latter phenotype shared only with the peb4 mutant ( Figures 1A–C,E ). This supports the hypothesis that VirK in C. jejuni may play a more general role in OM or cell surface biogenesis than reported in E. coli , where VirK is necessary, and potentially specific, for Pet toxin secretion (Tapia-Pastrana et al, 2012), a system absent in C. jejuni. …”
Section: Discussionsupporting
confidence: 87%
“…In E. coli VirK is thought to be a periplasmic chaperone for the plasmid-encoded toxin (Pet), an autotransporter produced by enteroaggregative E. coli (Tapia-Pastrana et al, 2012). While VirK in E. coli is periplasmic, Novik et al (2009) showed that the C. jejuni VirK homolog is associated with the inner membrane on the cytoplasmic face, and so may act as a chaperone prior to Sec-mediated export.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Blot overlay assays were performed as previously reported (43) with a few modifications. Purified proteins (EspC, His-NH 2 , His-Middle, His-COOH, His-EspCΔMiddle, and His-EspA) (1 µg) were separated by SDS-PAGE and transferred to PVDF membranes.…”
Section: Methodsmentioning
confidence: 99%
“…However, this discrepancy in results is not hard to reconcile if we observe the variable cytotoxic effect elicited by other class-I SPATEs [56, 64, 65, 67, 95] (discussed below), which also have distinctive degradation patterns on -spectrin—the target being linked to the cytotoxic effects [56, 64, 65]. Consequently, amino acid variation among SPATEs, protease doses, time of exposure, mammalian cell types, and bacterial strains from where SPATEs are purified [108, 109] may have influenced the strength of protease activity.…”
Section: Class-1 Spates the Cytotoxic Serine Proteasesmentioning
confidence: 99%